Effects of Different Harvesting Ages on Chemical Composition of Five Napier Grass (Pennisetum Purpureum) Varieties - Aini Kamaruddin, Nurul; Nadira Zulkifli, Aiza; Ahmad, Normala; Zakaria, Jamil (International Journal of Engineering and Technology, 2018)
The objective of this study is to determine the effects of the different harvesting ages (45 days, 60 days and 75 days) on the chemical composition of five Napier grass varieties. This research was conducted at Universiti Sultan Zainal Abidin (UniSZA) Farm in Pasir Akar, Besut, Terengganu. The proximate analysis was used to analyze the chemical compositions of moisture, ash, crude fiber, crude protein and fat, while the mineral compositions of magnesium, potassium, aluminium, phosphorus, and calcium were analyzed and measured using the dry ashing method and Induced Couple Plasma Optical Emission Spectrometry (ICP-OES). The findings of this study showed that most chemical compositions of five Napier varieties were decreased (p < 0.05) as harvesting age increased. The proximate compositions of all varieties show significantly decreased (p < 0.05) as age increased which is the moisture, ash, crude fiber, crude protein, and fat were decreased at age 75 days. Among the five varieties, Dwarf Napier shows the highest of crude protein (25.51%) followed by India Napier (22.44%), Uganda Napier (18.45%), Red Napier (18.26%) and Zanzibar Napier (16.78%), respectively. The mineral compositions of potassium and phosphorus of five varieties were decreased as age harvesting increased. Thus, this study showed that the harvesting ages affect to the chemical composition of the Napier grass and day 45 is the optimum age for harvesting which is providing high nutritive value of animal feed.Â Â Â